Diversity, Equity, Inclusion, Justice, and Antiracism Statements by Clinical Psychological Science Programs: A Mixed Methods Analysis of Public Commitments. - Rajesh, Aishwarya; Zhang, Ke Anne; Kelly, Chris; Aguilar Silvan, Yesenia; Diehl, Caroline K.; Obee, Averill F.; Wilson, Maria K.; Perez, Vanesa; Howard, Erica; Kang, Sungha; Duong, Jacqueline B.; Weiss, Hannah; et al. (Training & Education in Professional Psychology, 2023)
Clinical psychological science is long overdue to incorporate antiracism and social justice as core principles. To evaluate the current state of clinical science training programs' public-facing statements on antiracism and diversity, equity, inclusion, and justice (ADEIJ), we formed a workgroup under the guidance of the Academy of Psychological Clinical Science (APCS) Task Force to Center Racial and Social Justice in Clinical Science. Our workgroup evaluated the public-facing web materials of 78 APCS doctoral and internship programs. Following existing frameworks that have conceptualized the development of multicultural organizations, we evaluated the degree to which materials mentioned inclusivity, acknowledged inequities, and reported planned and enacted actions to promote ADEIJ. We examined rationales for engaging in this work, differentiating between moral and instrumental rationales. Results showed not all programs had ADEIJ statements, but a coding scheme can reliably assess existing statements. While all programs mentioned inclusivity and most acknowledged inequities, some had subtle or implicit exclusionary language, and a minority described concrete actions. Current efforts within our field may represent more symbolic than identity or structural change. Our findings inform recommendations for improving the efforts of training programs. Public Significance Statement: A coding scheme can reliably assess how clearly public-facing statements communicate a program's commitment to diversity, equity, inclusion, justice, or antiracist values. The programs assessed showed more indications of symbolic change than identity or structural change, perhaps reflecting a lack of knowledge about how to enact structural change and/or limited willingness to reflect on our field's contributions to historical and current inequities.